Sacrificial Dance of Ku Bua Mat : Rituals and Beliefs of Bankok, Borabue District, Mahasarakham - phanmanee, Piraporn (Journal for Developing the Social and Community, 2021)
The Sacrificial Dance of Ku Bua Mat is a pattern for the Ban Kok Kok community to be used as a community show and it is also a continuation of local culture that shows the cultural identity of the community, it also promotes cultural tourism of the province as well. Therefore, this research has the objective (1) to study the rituals, beliefs of Ban Kok, Borabue District Maha Sarakham Province that affects Ku Bua Mat, (2) to create a show the Koo Bua Mat Sacrificial Dance. This research used qualitative research methods by collecting data from documents, collecting data from the field. By surveying, interviewing, observing, and discussing group discussions and analyzing data, the research results were found that Koo Bua Mat is the archaeological site in small Khmer culture, Located at Ban Kok Kok, Tambon Buamas, Amphur Borabue, Maha Sarakham Province. The architecture is a single castle, with a base, north connecting the main castle to enshrine Vishnu’s idol which such architectural styles are rarely seen in the Khmer city of Phra Nakhon, creation it is not known how the belief in the creation was established. For the most part, religious places built in Khmer culture were Often built as a single castle alone for Lord Shiva, or built as three castles for Lord Shiva, Vishnu and Brahma respectively. The show the Koo Bua Mat Sacrificial Dance: principles of the invention in thinking for the dancer in the community. Defining key ideas at both target and objective levels, processing data, setting boundaries, formatting as well as defining other elements that include the costumes, the music, the dances, all are processes that control the work of the creation according to the purpose and concept which Creativity must include thoughtfulness, agility, flexibility, initiative, and tact.